Toxoplasma gondii en los gatos del cantón Latacunga - Alvear Cajiao, Jessica Victoria (2017)
The present research project is about "Toxoplasma gondii in cats of the LATACUNGA Canton" whose purpose is to diagnose the degree of vulnerability of the domestic cat, determining the lack of knowledge of the owners, whose specific objectives are: perform a scientific review on the prevalence of Toxoplasmosis, estimate the domestic cat population in the 2010 to 2015 period and determine the degree of knowledge of the owners about Toxoplasmosis through the application of a survey. A survey of 150 surveys was carried out on the people of the parishes of the LATACUNGA Canton, where the inhabitants of the different sectors were very well received, with the result that most cats have never presented any type of disease. The impact generated in this project helped to identify the lack of a real database that provides true information by the Public Health Ministry, given the importance of determining the prevalence of Toxoplasmosis disease presented in domestic cats. Taking into account that it is a serious disease being a big problem for animals as well as for people causing serious injuries especially for pregnant women and for the fetuses, being transmitted by feces and by factors of ingestion of raw or badly cooked food.